PELUANG MAHASISWA DALAM DUNIA KERJA DITINJAU DARI ASPEK KOMPETENSI - Tri Rinawati; Asih Niati; Teguh Ariefiantoro (BBM (Buletin Bisnis & Manajemen), 2021)
The research objective is to determine the absorption of labor in terms of competencyaspects and to determine the relevance of the world of education in terms of competence withthe world of work. This type of research is qualitative. The sampling of data sources was done bypurposive and snowball. Data collection techniques by using triangulation (combined). The dataanalysis is inductive or qualitative in nature and the research results emphasize meaning ratherthan generalization. Students opportunities in the world of work in terms of competence are verylow, this can be shown based on data on the increase in the number of the workforce which isnot accompanied by an increase in the labor force participation rate. It is hoped that theAcademics will open an entrepreneurship-based curriculum where every student is expected tohave the ability and potential to become an entrepreneurial spirit. The relevance of the world ofeducation in terms of competence with the world of work is still low even though public access tohigher education continues to increase. This is reflected in the low labor absorption of collegegraduates. The relevance of college graduates to the need for labor is an important factor inefforts to prevent unemployed graduates, in this case it is necessary to determine strategicpolicies and superior programs in order to realize quality higher education.